Principals' leadership behaviours practices at secondary schools in Sri Aman, Sarawak / Leo Watson Anak Nicholas Nyalong - Nicholas Nyalong, Leo Watson (2014)
The purpose of this study was to identify principals' leadership styles in secondary schools in Sri Aman, Sarawak. Two secondary schools from urban and rural area were selected for the study. Data were collected using questionnaire and interview techniques. The questionnaire was distributed to a total of 188 randomly selected teacher respondents and 155 questionnaires were returned. Data were analysed using descriptive and inferential statistics. The principals' leadership styles of this study are idealized influence-attribute, idealized influence-behaviour, inspirational motivation, intellectual stimulation, individualized consideration, contingent reward, management by exception active, management by exception-passive, laissez-faire leadership, extra effort, effectiveness, and satisfaction. The data reveals that transformational leadership components were practiced at a frequent level by principals. On the other hand, transactional leadership components were still practiced by principals but at a moderate level and principals show low interest in incorporate Laissez-Faire leadership. Furthermore, teachers' gender, and secondary schools' location do not influence the level of leadership behaviours components practiced by principals. Additionally, teachers from different years in service perceived that principals' leadership behaviour increases when teachers' year in service increase, for example, principals' idealized influence attribute, Laissez-Faire leadership, effectiveness and satisfaction. But in overall, there were no significant difference of others principals' leadership behaviours. Besides, teachers from different teaching departments perceived that although the principals' leadership behaviours were frequently practiced, different teaching departments may have different needs and focus depending types of principals' leadership behaviours. Finally, principals were reported practiced both transformational and transactional leadership with transformation leadership was highly practiced in compared to transactional leadership components. Based on the findings, this study also provides recommendations for improvement of practices and future research.